200k views
4 votes
Identify the equivalent expressions of 4(2x + x-3) - 3x + 3 by substituting x = 2 and x = 3.

9x - 9
9x - 1
9x + X-9
9(x - 1)
4(3x - 3) + 3 - 3x

User Dikirill
by
5.7k points

2 Answers

1 vote

Answer:

9

18

Explanation:

x = 2:

4(4 + 2 - 3) - 6 + 3 = 12 - 6 + 3 = 9

x = 3:

4(6 + 3 - 3) - 9 + 3 = 24 - 9 + 3 = 18

User Allan S
by
4.6k points
1 vote

Answer:

9x -9

9(x - 1)

4(3x-3) - 3x + 3

Explanation:

4(2x + x-3) - 3x + 3

Combine like terms

4(3x-3) - 3x + 3

Distribute

12x -12 -3x+3

Combine like terms

9x -9

Factor out 9

9(x-1)

User Calvin Alvin
by
5.6k points